2014
DOI: 10.4236/ojgen.2014.42013
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Frequencies of HLA Class I and Class II Genes of an East African Population

Abstract: Human Leukocyte Antigens (HLAs) play an important role in host immune responses to infectious pathogens, and influence organ transplantation, cancer and autoimmune diseases. In this study we conducted a high resolution, sequence-based genotyping of HLA class I and class II genes of more than 2000 women from Kenya, eastern Tanzania and southern Uganda around Lake Victoria and analyzed their allele, phenotype and haplotype frequencies. A considerable genetic diversity was observed at both class I and II loci. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Comparing the results with other studies, the allele frequency observed in Group 2 was similar to other studies performed with Caucasian populations (Delfino et al ., ; Moya‐Quiles et al ., ; Balas et al ., ). On the other hand, the frequency observed in Group 3 can be compared with African descent populations (Nigam et al ., ; Tu et al ., ; Peterson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Comparing the results with other studies, the allele frequency observed in Group 2 was similar to other studies performed with Caucasian populations (Delfino et al ., ; Moya‐Quiles et al ., ; Balas et al ., ). On the other hand, the frequency observed in Group 3 can be compared with African descent populations (Nigam et al ., ; Tu et al ., ; Peterson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…[32][33][34] On the other hand, the frequency of DQ2 was higher than the results of studies from Iran (20%), Turkey (18%), Southern India (12.78%), Rwanda (15.5%), Tanzania (13.5%) and Cameroon (7.0%), [32][33][34] but lower compared with a study on the Saharawi population (39%), where the prevalence of the celiac disease has been estimated to be the highest in the world. 35 Our study also showed that the DQ8 haplotype was less frequently found among the Ethiopian children as compared with the Swedish references (6.8% vs 13.1%), but comparable with study findings from Japan (7.6%), Sardinia (5%) 33 and 8.9% of Caucasians in the United States. 36 In addition, we found a higher distribution of DQ8 than in South Africa (2.8%), Saharawi (2.7%), Algeria (2.2%), Italy (2%) and Cameroon (0.6%).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that cross-reactive memory B-cell responses were primed after 2009 pdmH1N1 infection [ 29 ] and activation of NP-specific T-cell response by MVA-NP+M1 in human NALT [ 30 ]. Because M1 contains major immunodominant CD8 + T-cell epitopes and HLA-A2 is among the most common HLA alleles (20%–30%) [ 31 ], we examined HLA-A2 restricted M1 58–66 peptide-specific CD8 + T-cell responses in adenotonsillar tissue after MVA-NP+M1 stimulation. We showed that MVA-NP+M1 elicits marked increases in M1-specific CD8 + T cells, including T RM cells, which exhibit rapid degranulation and target cell killing on recall antigen recognition.…”
mentioning
confidence: 99%